Geospatial Analysis of Malnutrition among Under-Five Children: A Scoping Review - Dmello, Mackwin Kenwood; Badiger, Sanjeev; Kumar, Sudeep; Galey, Karma; Kumar, Nanjesh; Dsouza, Neevan (Journal of Health and Allied Sciences NU, 2023)
Nutritional status is one of the important factors that indicate children's proper development and growth. The geospatial analytic approach is useful in describing and analyzing the characteristics, depth, and coverage of the malnutrition burden among under-five children. This current scoping review was performed to systematically map the spatial analytical techniques and approaches applied in nutrition among under-five children. An organized online database search was conducted to identify articles published between 1995 and 2021 on under-five nutrition and spatial statistic in PubMed, Science Direct, Scopus, and Web of Science. A total of 80 distinct articles were identified, of which 34 articles were used for the final review. A spatial statistical correlation was mainly used (n = 15), followed by Bayesian spatial modelling (n = 7), Global Moran's technique (n = 9), and Getis-Ord (n = 3). Nine studies in India concerning spatial analysis and undernutrition were conducted based on a national-level demographic health survey. There is a need for future spatial studies related to nutrition and under-five children at the sub-national level in India.
Keywords: geographic information system; nutrition; spatial methods